Implementing the English health inequalities agenda: addressing challenges to person-level, cross-sectoral data linkage, access and routine use for local authority public health - George, Abraham; Powell, Richard; Rao, Mala (International Journal of Population Data Science, 2024)
Local authorities are central to the implementation of English Integrated Care Systems' health inequalities agendas, embedding public health into population health management planning. They work with partners to deliver a range of 'health determinant' services and facilities for people in a defined geographic area. This work is substantially premised on the use of cross-sectoral data that is linked at the individual level, readily available, longitudinal and contemporaneous. However, multiple challenges exist to such data availability. This paper elaborates upon these challenges to local authority public health systems and their potential solutions.